Force Control Strategies in Hydraulically Actuated Legged Robots. (10th March 2016) - Montes, Hector; Armada, Manuel
In this contribution, several strategies of force control have been proposed to be implemented and evaluated in ROBOCLIMBER, a quadruped robot of large dimensions. A first group of strategies proposed in this paper is based on impedance control, which is intended to adapt the foot-ground contact forces according to the experimentally specified damping ratio and the undamped natural frequency. A second control strategy of interest for many practical cases is called the parallel force/position control, which has one inner loop position control and two external control loops, one of force and another of position. A third group of control strategies is the posture stabilization for ROBOCLIMBER using the feedback of the ZMP calculation and the position of its legs. Finally, a control strategy for the control of a quasi-static gait using ZMP feedback is proposed and tested by simulation.